Optimizing Arabic Language Proficiency Through Instagram Social Media as an Effort in Arabic Language Digitalization - Fahrun Nisa', Anita Lailatul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Technology is developing rapidly and affects all aspects of life, especially in the field of education. One form of technological development that exists is the emergence of various social media applications as a means of learning, especially Instagram. As an effort to digitize Arabic, Instagram is used optimally as a practical Arabic learning medium. This study uses a qualitative descriptive method that aims to describe and describe how Arabic learners can improve Arabic language skills through Instagram. The results showed that as an effort to improve Arabic language skills, Instagram is an applicable learning medium. There are 5 Arabic learning recommendation accounts, namely 1) @arabiyahtalks; 2) @muslikhin_m; 3) @marhaban.academy; 4) @nahwu_pedia; and 5) @uslubarabi.id. The content uploaded in several accounts is considered quite varied, practical, easy to understand, and up to date. Efforts to maximize Arabic language skills can be done by following some material packaged in various forms of features on Instagram by several Arabic learning accounts.